Sensitivity of transformation to small differences in population density during serial passage of NIH 3T3 cells. - Yao, A (1992)
Early passages of the NIH 3T3 mouse cell line undergo spontaneous neoplastic transformation leading to the development of transformed foci if grown to confluence in 2% (vol/vol) calf serum (CS) and left there for more than a week. Transfer of the postconfluent cultures results in the appearance of large numbers of transformed foci; many of them are larger and denser than those in the original culture. If the cells are continually kept at low population densities by frequent passages in 10% CS, they lose the capacity to undergo spontaneous transformation. If however the low-density passages are made in 2% CS or in 10% (vol/vol) fetal bovine serum, both of which support lower growth rates and saturation densities than does 10% CS, they gain the capacities to grow to high saturation densities and produce more foci when grown to confluence in 2% CS. These increases are proportional to the population densities used in the frequent passages, although the densities are all kept well below confluence. We conclude that the combined constraints of submaximal serum plus those of the limited cell contacts of the low cell densities used here elicit an adaptive response that endows the entire population with increased growth capacity. The increased growth capacity of the heterogeneous population in turn increases the capacity of a fraction of the population to initiate distinctive transformed foci. Similar studies have indicated that the capacity of cells to produce tumors and metastases in mice and rats is enhanced by prior maintenance at high density in culture. We propose the concept of progressive state selection to account for the general increase in the growth capacity of cells that is elicited by moderate constraints on their growth and metabolism.